Recommendation and safety of vaccinacion in patients with rheumatoid arthritis using immunosuppressive treatment (Research, Society and Development, 2021)
Introduction: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease often treated using immunosuppressive drugs that are directly related to the occurrence of opportunistic manifestations. Therefore, vaccination can be a means of protection, but its safety and recommendation must be evaluated. Objective: To identify the safety and recommendation of vaccination in patients treating RA. Method: Integrative literature review, developed from 11 articles obtained from the PubMed® database, and 3 articles obtained from the BVS library in which the same descriptors were used in Health Sciences, totaling 14 analyzed works, a time frame was defined, covering articles from the last 5 years. Results: According to the findings, the main recommended and safe vaccines are Pneumococcal, Influenza, Hepatitis B, Human Papilloma Virus (HPV) and Herpes Zoster. However, attention must be paid to the interaction between vaccine-drug, as this relationship can cause damage to the performance of the vaccine or even harm to the patient. Conclusion: Based on the analyzed studies, it is concluded that vaccination is generally recommended and safe for individuals with rheumatoid arthritis undergoing treatment with immunosuppressants.